Analysis of the Implementation of Hospital Management Information Systems (SIMRS) to Improve the Quality of Pharmaceutical Services: Literature Review - Astuti, Rina; Theresia (Dinasti International Journal of Digital Business Management, 2025)
Hospital Management Information System (SIMRS) is a communication information technology that integrates and processes the entire flow of hospital service processes. SIMRS currently has a very important role in hospital management because it can help manage hospital operations both in data processing and patient service activities. This research is intended to analyze the implementation of the Hospital Management Information System (SIMRS) in order to improve the quality of services in hospitals, especially pharmaceutical services. The research uses a qualitative method with a literature review approach that analyzes various literature sources relevant to the topic of implementing the Hospital Management Information System (SIMRS) which has an important role in improving the quality of pharmaceutical services in hospitals. The results of the analysis show that the implementation of SIMRS can improve the efficiency of drug management, prescription accuracy and patient therapy monitoring. The success of SIMRS implementation is influenced by careful planning, user training, and system maintenance. This research contributes to the development of SIMRS implementation strategies to improve the quality of pharmaceutical services.